Pengaruh Tingkat Suku Bunga dan Return On Assets terhadap Keputusan Berinvestasi pada Aplikasi Bibit di Sulawesi Selatan - Awal, Jumadil; Puspitasari, Ayu; Satria, Yudi (Tangible Journal, 2025)
This study aims to determine the effect of interest rates and return on assets on investment decisions in the Bibit app in South Sulawesi. This study used a quantitative approach with a random sampling technique and involved 96 Bibit user respondents. The results showed that interest rates and return on assets had a positive and significant effect on investment decisions. An increase in interest rates and Return on Assets (ROA) significantly encourages investment decisions. Higher interest rates signal the potential for attractive returns, while a higher ROA reflects good company performance, thereby increasing investor confidence.